Numerical simulation and analysis of the propagation of a prefrontal squall line - Cram, Jennifer M., author (Colorado State University. Libraries, 1990)
An observational and numerical study of the squall line that occurred on 17-18 June 1978 is described. This squall line was initially triggered by the strong surface convergence along a cold front, and stretched from Illinois to the Texas panhandle. The squall line was aligned with the surface front during its initial development (at 0000 UTC 18 June 1978), but then propagated faster than the front, resulting in a separation of approximately 200 km by 0300 UTC and 300-400 km by 0600 UTC. The CSU RAMS model is used to model the squall line development and propagation. Several sensitivity experiments were completed to test the sensitivity of the results to the use of the Kuo-type cumulus parameterization scheme and grid-scale microphysical processes. The simulations that included the cumulus parameterization scheme and grid scale latent heating or condensation effects accurately modelled the initial development of the squall line and its subsequent movement away from the front. The effects of the gridscale microphysical processes (versus the more simple grid-scale condensation and latent heat release) were m:nor in these simulations. A simulation to test the effects of varying the initial specification of roughness length zo, soil texture, and soil moisture was also completed. The results were very similar to the results with a non-varying specification of zo and soil texture, especially in the region of the squall line. Greater differences were found to the east of the squall line where the convection was not as strongly forced by the dynamics. The propagation of the squall line in the model is shown to be due to the propagation of a deep tropospheric internal gravity wave, in a wave-CISK-like process. The thermal and dynamic perturbations associated with the hypothesized wave are shown to be consistent with gravity wave theory, and the characteristics of the wave are compared to similar results from wave-CISK studies. The wave is forced by the heating profile associated with the convection and propagates southeastward at 18 m s-1 with a horizontal wavelength of ~200 km and a vertical wavelength of 10 km. The wave maintains its coherence and energy through the quasi-resonant effects of reflection from the stability discontinuity at the tropopause and a low-level layer in which the Scorer parameter is very small. The wave dissipates when the heating maximum associated with the wave forcing widens and rises so that the resonant effect is diminished. A critical layer also develops in the upper atmosphere at about the same time, which acts to absorb the wave energy. The propagation of the squall line as an internal gravity wave is discussed in relation to other studies. The current literature favors the mechanism o gust front convergence to explain squall line propagation, although there are a few other modelling studies that show specific instances of squall line propagation as being due to internal gravity waves. It is suggested that a spectrum of scales of forcing may exist and be responsible for squall line propagation, but many models and observations may be able to detect only the gust-front- type processes. The 17-18 June 1978 squall line probably did not propagate solely as the result of any one mechanism, but instead as the product of several active mechanisms. The dominant mechanism in these modelling simulations was an internal gravity wave, and it seems reasonable that the gravity wave was at least one of the mechanisms responsible for the actual propagation of the 17-18 June 1978 squall line.
Fall 1990.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1990.
Keywords: Squall lines; Fronts (Meteorology)